2019
DOI: 10.1038/s41598-018-36731-3
|View full text |Cite|
|
Sign up to set email alerts
|

Claudin-3-deficient C57BL/6J mice display intact brain barriers

Abstract: The tight junction protein claudin-3 has been identified as a transcriptional target of the Wnt/β-catenin signaling pathway regulating blood-brain barrier (BBB) maturation. In neurological disorders loss of claudin-3 immunostaining is observed at the compromised BBB and blood-cerebrospinal fluid barrier (BCSFB). Although these observations support a central role of claudin-3 in regulating brain barriers’ tight junction integrity, expression of claudin-3 at the brain barriers has remained a matter of debate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 69 publications
3
60
0
Order By: Relevance
“…As first step for the comprehensive barrier target analysis the relative expression of these targets was assessed in hCMEC/D3 under standard growth conditions. In the BBB research field the claudins-1, -3, -5, -11 and -12 are mostly investigated as surrogate markers for TJs, whereas recent studies with knock-out mice raised doubts about the presence and role of claudin-3 and -12 at the BBB [7,8]. In the last 2 to 3 years some reports with expression data of primary human BCECs and hiPSC-BCECs have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As first step for the comprehensive barrier target analysis the relative expression of these targets was assessed in hCMEC/D3 under standard growth conditions. In the BBB research field the claudins-1, -3, -5, -11 and -12 are mostly investigated as surrogate markers for TJs, whereas recent studies with knock-out mice raised doubts about the presence and role of claudin-3 and -12 at the BBB [7,8]. In the last 2 to 3 years some reports with expression data of primary human BCECs and hiPSC-BCECs have been published.…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, however, there is a lively discussion about the role of individual claudins at the BBB. For example, it was recently shown that the claudins-3 and -12 in the BBB of the mouse do not have the previously believed importance for BBB function [7,8]. In addition, there are postulated species differences that make it difficult to get a clear picture of which claudins are present in the human BBB and which function they fulfill [3].…”
Section: Introductionmentioning
confidence: 99%
“…We removed multiple claudins using the C‐CPE reagent because removal of single C‐CPE‐sensitive claudins has not generated severe renal developmental phenotypes, suggesting there may be functional redundancy amongst members and/or different requirements depending on the model organism. For example, removal of Claudin‐3, −4, −6, or −8 has not led to any defect in mouse kidney development based on the fact that the offspring survive and do not succumb to renal failure postnatally (Anderson et al., 2008; Castro Dias et al., 2019; Fujita, Hamazaki, Noda, Oshima, & Minato, 2012; Gong et al., 2015). In the absence of comprehensive counts of nephron number, however, we cannot rule out the possibility that the mice may have mild to moderate defects in nephron number from a deficiency in renal branching morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Central components of tight junctions are claudins (Cldn), tetraspanning membrane proteins, of which Cldn5 is found in vessels in all organs ( Morita et al, 1999 ). Expression of Cldn3, Cldn12, and Cldn1 in brain capillary endothelial cells is rather controversial ( Ohtsuki et al, 2008 ; Tietz and Engelhardt, 2015 ; Vanlandewijck et al, 2018 ), and while Cldn3 is inducible during mouse brain angiogenesis ( Liebner et al, 2008 ) it is clearly absent in adult brain endothelium ( Castro Dias et al, 2019 ). Occludin is another bona fide tight junction component of endothelial and epithelial cells, however, its gene inactivation does not cause obvious defects in the vasculature ( Saitou et al, 2000 ).…”
Section: Composition Of Adhesion Molecules At Endothelial Junctionsmentioning
confidence: 99%